Climate policy without a price signal: Evidence on the implicit carbon price of energy efficiency in buildings - Ghislaine Lang; Bruno Lanz (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
In the absence of a global carbon price, many individual countries set up policies to incentivize specific abatement interventions. In turn, minimizing compliance cost requires policy-makers to identify interventions that are worth pursuing. With this in mind, the objective of this paper is to document heterogeneity in the price of carbon implicitly associated with a range of interventions to improve buildings' energy efficiency. We use data for a portfolio of 548 multi-unit buildings observed over 16 years, representing 12,820 rental units, and quantify the impacts of more than 400 energy efficiency interventions among 240 treated buildings. We exploit variation in the timing of investments to provide evidence that treated and control buildings follow the same trend in the absence of energy efficiency investments, and use staggered difference-in-differences regressions to document building-level energy savings, CO2 abatement, and heating expenditure reductions. Our results indicate significant heterogeneity in energy savings across interventions, and suggest that the implicit price of carbon associated with frequently subsidized measures (such as wall insulation and windows replacement) is well in excess of available benefit estimates for avoided emissions.
Keywords: H21; H23; Q41; Q49; Q58; R31; 330; Regulation; climate policy; implicit carbon price; energy efficiency investments; energy savings; staggered design